The Differentiation in vitro of Human Tonsil B Cells With the Phenotypic and Functional Characteristics of T-bet+ Atypical Memory B Cells in Malaria - Ambegaonkar, Abhijit A.; Nagata, Satoshi; Pierce, Susan K.; Sohn, Haewon (Frontiers in Immunology, 2019)
Malaria is a deadly infectious disease associated with fundamental changes in the composition of the memory B cell (MBC) compartment, most notably a large expansion of T- bet+ MBCs, termed atypical MBCs. However, we know little about the precursors of atypical MBCs and the conditions that drive their differentiation. We compared the responses of human tonsil naïve B cells, MBCs and germinal center B cells to a variety of stimulatory conditions. We determined that persistent antigen presentation in the presence of CpG and IFN-γ induced maximal expression of T-bet and other phenotypic markers of malaria-associated atypical MBCs primarily in naïve B cells in vitro. Importantly T-bet+ naïve-derived B cells resembled atypical MBCs in their hypo-responsiveness to signaling through their B cell receptors. Thus, naïve B cells can be induced to differentiate into phenotypically and functionally atypical-like MBCs in vitro under conditions that may prevail in chronic infectious diseases in vivo.